Gender, health and ageing in Fiji: a mixed methods analysis - Rebecca Dodd; Janani Shanthosh; Thomas Lung; Aporosa Robaigau; Mai Ling Perman; Eric Rafai; Roslyn Poulos; Anthony B. Zwi; Renu John; Anna Palagyi (BMC, 2021)
Abstract Background Women are disadvantaged by ageing: older women are more likely than older men to suffer from ill-health, have less access to health care and suffer discrimination within the health care system. Globally, there is a dearth of health research on gender and ageing with substantial knowledge gaps in low and middle-income country contexts. Part of a wider investigation on health and ageing in Fiji, our objective was to identify and describe gendered differences in healthy ageing in this Pacific Island context. We believe this to be the first such study in the Pacific region. Methods Applying a health systems lens, we used a mixed-methods approach, encompassing analysis of cause of death data; focus group discussion to gather community and family attitudes to health services; and policy analysis, and then used data triangulation techniques to draw out key themes and insights. Results We found that gender affects health outcomes among older persons, attitudes towards and experience of healthy ageing, and an older person's access to and use of health services. We also found that while Fiji's policy response to ageing has recognised the importance of gender, to-date there has been limited action to address gender differences. Gender (as oppose to sex differences) has direct and indirect implications for the health of older Fijians, while gendered inequalities and patriarchal norms appear to affect both men and women's experience of ageing and the health system response. Further, gender and age discrimination may be intersecting, intensifying their separate effects. Conclusion This study demonstrates the feasibility and importance of applying a gender lens to the study of healthy ageing. Our findings from Fiji may be relevant to other island nations in the south Pacific which share similar challenges of population ageing, a constrained health budget and geographically-dispersed populations. The data triangulation methodology may be considered an efficient and insightful way to examine gendered responses to healthy ageing elsewhere.